The effect of GeoGebra android on increasing mathematical understanding ability based on gender - Rizki Dwi Siswanto; Dadan Dasari; Agus Hendriyanto; Lukman Hakim Muhaimin; Rahmat Kusharyadi; Sani Sahara (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
This study aims to describe the increase of students' mathematical understanding ability in learning the two-variable linear equation system (SPLDV) and the two-variable linear inequality system (SPTLDV) with Android GeoGebra media reviewed by gender. This experimental quasi research is one group pretest postest design. The sample in this study was a class XI of 32 students with Purposive Random Sampling techniques. Data collection in this study uses an instrument for a mathematical understanding ability test in the form of a description. The results of the study can be concluded in the learning of Android GeoGebra, the mathematical understanding of male students is significantly different from the mathematical understanding of female students. It means that in learning the Android GeoGebra Improvement of the Mathematical Understanding Ability of Male Students is greater than female students. Thus it can be concluded that in the learning of Android GeoGebra, an increase in the mathematical understanding of male students is better than female students.